The effect of eucalyptus vapor on cough after coronary artery bypass surgery - Somayeh Zare; Masoumeh Bagheri-Nesami; Hedayat Jafari; Jamshid Yazdani Charati; Valiollah Habibi (Mazandaran University of Medical Sciences, 2017)
Cough is postoperative complication following endotracheal intubation as well as inflammation of the pharynx, larynx and trachea. The aim of this study was to evaluate the effect of eucalyptus vapor on cough after tracheal extubation in patients undergoing coronary artery bypass graft (CABG). In this randomized controlled trial, 100 patients undergoing CABG were randomly divided into two groups by accessible sampling. Before the intervention and after tracheal extubation, demographic and clinical data, as well as data on cough by a scoring system were collected from interventional and control groups. The patients in the interventional group after tracheal extubation were exposed to eucalyptus vapor for about 10 min. This treatment was performed at 1 and 12 h after extubation. The severity of cough was recorded in both interventional and control groups at 0, 1, 6, 12 and 24 h after extubation. The present study showed that the severity of cough after extubation in the patients undergoing CABG in the interventional group had no significant difference at the times of immediate to 24 hours after extubation. Risk of cough had respectively 9.5% increase in the control group as compared to the interventional group.